Beetroot, A Remarkable Vegetable: Its Nitrate and Phytochemical Contents Can be Adjusted in Novel Formulations to Benefit Health and Support Cardiovascular Disease Therapies - dos S. Baião, Diego (Antioxidants (Basel), 2020)
The cardioprotective effects of dietary nitrate from beetroot in healthy and hypertensive individuals are undeniable and irrefutable. Nitrate and nitrate-derived nitrite are precursors for nitric oxide synthesis exhibiting an effect on cardiomyocytes and myocardial ischemia/reperfusion, improving endothelial function, reducing arterial stiffness and stimulating smooth muscle relaxation, decreasing systolic and diastolic blood pressures. Beetroot phytochemicals like betanin, saponins, polyphenols, and organic acids can resist simulated gastrointestinal digestion, raising the hypothesis that the cardioprotective effects of beetroots result from the combination of nitrate/nitrite and bioactive compounds that limit the generation of reactive oxygen species and modulate gene expression. Nitrate and phytochemical concentrations can be adjusted in beet formulations to fulfill requirements for acute or long-term supplementations, enhancing patient adherence to beet intervention. Based on in vitro, in vivo, and clinical trials, beet nitrate and its bioactive phytochemicals are promising as a novel supportive therapy to ameliorate cardiovascular diseases.